Neuroinflammation in glaucoma: a myriad of cellular pathways and players - Michael MacLean; Sean D. Lydon; Cátia Gomes; Elizabeth M. Pizzi; Cory A. Diemler; Sarah E. R. Yablonski; Gareth R. Howell; Jason S. Meyer; Richard T. Libby (Mammalian Genome, 2026)
Glaucoma is a complex neurodegenerative disease with multiple subtypes, yet all are characterized by the progressive dysfunction and loss of retinal ganglion cells (RGCs), which ultimately results in vision impairment and blindness. Elevated intraocular pressure (IOP) is a major risk factor for glaucoma; however, it is neither necessary nor sufficient for glaucomatous neurodegeneration, as patients can exhibit high IOP without developing glaucoma and patients can develop glaucoma with normal IOP. Yet FDA-approved treatment options are largely limited to approaches to minimize risk and reduce IOP. Thus, there is a critical need to target other aspects of glaucoma pathophysiology. Neuroinflammation is broadly defined here as immune-relevant responses, often involving microglia and astrocytes, within the central nervous system which may include peripheral immune cell infiltration. Burgeoning evidence has implicated glia in the development and progression of glaucoma in human tissues and mouse models. Most mouse models of glaucoma to date have shown that microglia and astrocytes are reactive in early stages of glaucomatous neurodegeneration prior to overt RGC loss. However, there is growing evidence that human and mouse glia adopt distinct phenotypes in response to neurodegeneration. Thus, there is critical need to expand our studies to include the new generations of human cell culture models. In this review, we discuss: 1) the evidence of neuroinflammatory processes in human glaucoma; 2) models of glaucoma relevant neuroinflammation; and the evidence specifically for 3) innate immune cell-driven and 4) macroglia-driven processes.

Adaptive area-wide management for suppressing spruce budworm outbreaks: effectiveness of the early intervention strategy - Rob C. Johns; S. Edwards; L. Amos-Binks; J. J. Bowden; D. Carleton; C. Edge; C. Hennigar; P. James; D. MacLean; V. Martel; E. R. D. Moise; B. Morin; et al. (Journal of Pest Science, 2026)
In eastern North America, two main insecticide-based strategies are used to manage spruce budworm ( Choristoneura fumiferana ) outbreaks. The traditional ‘Foliage Protection Strategy’ (FPS) focuses on temporarily reducing defoliation and tree mortality in high-value stands, allowing outbreaks to progress naturally in surrounding areas. The ‘Early Intervention Strategy’ (EIS) is an adaptive, area-wide management approach that targets low-density “hotspots” to prevent outbreak growth and spread. We report findings from a 10-year case study (2015–2024) in Atlantic Canada assessing EIS effectiveness. EIS treatments consistently reduced population growth rates, resulting in a 12–67% reduction in hotspot areas compared to untreated areas. Crucially, this suppression curbed the rise and spread of the outbreak across northern New Brunswick, with negligible defoliation observed throughout the study period. By comparison, in a neighboring Quebec study area contemporaneously managed with FPS, the outbreak advanced normally, causing moderate to severe defoliation over ~ 1.7 million hectares by 2024. Moreover, EIS required ~ 80% less insecticide, with 66% of treated areas receiving treatment in only a single year, compared with just 15% under FPS. Our findings provide robust evidence for the effectiveness of EIS when implemented under suitable conditions, highlighting its potential as a proactive outbreak management approach.

Multimorbidity as a predictor of mortality in companion dogs - Eric R. Foreman; Laura Corlin; Kate E. Creevy; Jessica M. Hoffman; Joshua M. Akey; Rozalyn M. Anderson; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Matthew D. Dunbar; Virginia R. Fajt; Erica C Jonlin; et al. (GeroScience, 2026)

The effects of muscle temperature on the muscle blood flow-oxygen consumption relationship during single leg isokinetic exercise - Dominique D. Gagnon; Alexus McCue; Juha E. Peltonen; David Marsh; David MacLean; Olivier Serresse (Journal of Thermal Biology, 2025)

Combination antiretroviral therapy prevents SIV-induced aging in the hippocampus and neurodegeneration throughout the brain - Miranda D. Horn; Alison R. Van Zandt; Cecily C. Midkiff; Ahmad A. Saied; Andrew G. MacLean (Journal of NeuroVirology, 2025)
Virus-induced accelerated aging has been proposed as a potential mechanism underlying the persistence of HIV-associated brain injury (HABI) despite advances in access and adherence to combination antiretroviral therapies (cART). While some studies have demonstrated evidence of accelerated aging in PLWH, studies examining the effects of cART intervention are limited, with most studies being in vitro or utilizing small animal models. Here, we utilized archival FFPE tissues from Simian immunodeficiency virus (SIV) infected rhesus macaques to assess the levels of two proteins commonly associated with aging - the cellular senescence marker p16 INK4a (p16) and the NAD-dependent deacetylase sirtuin 1 (SIRT1). Our central hypothesis was that SIV infection induces accelerated aging phenotypes in the brain characterized by increased expression of p16 and SIRT1 that correlate with increased neurodegeneration, and that cART inhibits this process. We found that SIV infection induced increased GFAP, p16, SIRT1, and neurodegeneration in multiple brain regions. Importantly, cART reduced SIV-induced accelerated aging (p16 and SIRT1) in the hippocampus and neurodegeneration and GFAP expression in the frontal lobe. Combined, these data suggest that cART is both safe and effective in reducing neuroinflammation and age-associated alterations in astrocytes that contribute to neurodegeneration, providing possible therapeutic targets in the treatment of HABI.

Aquatic occurrence, fate and potential ecotoxicity of insecticide and fungicide residues originating from a biofuels production facility using pesticide-treated seeds - Jascika A.A. Maclean; Shannon Bartelt-Hunt; Daniel D. Snow; Josephus F. Borsuah; Raquel Wielens Becker; Moushumi Hazra (Journal of Hazardous Materials, 2025)

Test of Rapamycin in Aging Dogs (TRIAD): study design and rationale for a prospective, parallel-group, double-masked, randomized, placebo-controlled, multicenter trial of rapamycin in healthy middle-aged dogs from the Dog Aging Project - Amanda E. Coleman; Kate E. Creevy; Rozalyn Anderson; May J. Reed; Virginia R. Fajt; Kathleen M. Aicher; Genna Atiee; Brian G. Barnett; Ryan D. Baumwart; Beth Boudreau; Suzanne M. Cunningham; Matthew D. Dunbar; et al. (GeroScience, 2025)

Mechanistic microclimate models and plant pest risk modelling - Jonathan R. Mosedale; Dominic Eyre; Anastasia Korycinska; Matthew Everatt; Sam Grant; Brittany Trew; Neil Kaye; Deborah Hemming; Ilya M. D. Maclean (Journal of Pest Science, 2024)
Climatic conditions are key determining factors of whether plant pests flourish. Models of pest response to temperature are integral to pest risk assessment and management, helping to inform surveillance and control measures. The widespread use of meteorological data as predictors in these models compromises their reliability as these measurements are not thermally coupled to the conditions experienced by pest organisms or their body temperatures. Here, we present how mechanistic microclimate models can be used to estimate the conditions experienced by pest organisms to provide significant benefits to pest risk modelling. These well-established physical models capture how landscape, vegetation and climate interact to determine the conditions to which pests are exposed. Assessments of pest risk derived from microclimate conditions are likely to significantly diverge from those derived from weather station measurements. The magnitude of this divergence will vary across a landscape, over time and according to pest habitats and behaviour due to the complex mechanisms that determine microclimate conditions and their effect on pest biology. Whereas the application of microclimate models was once restricted to relatively homogeneous habitats, these models can now be applied readily to generate hourly time series across extensive and varied landscapes. We outline the benefits and challenges of more routine application of microclimate models to pest risk modelling. Mechanistic microclimate models provide a heuristic tool that helps discriminate between physical, mathematical and biological causes of model failure. Their use can also help understand how pest ecology, behaviour and physiology mediate the relationship between climate and pest response.

Proximal microclimate: Moving beyond spatiotemporal resolution improves ecological predictions - David H. Klinges; J. Alex Baecher; Jonas J. Lembrechts; Ilya M. D. Maclean; Jonathan Lenoir; Caroline Greiser; Michael Ashcroft; Luke J. Evans; Michael R. Kearney; Juha Aalto; Isabel C. Barrio; Pieter De Frenne; et al. (Global Ecology and Biogeography, 2024)
Aim The scale of environmental data is often defined by their extent (spatial area, temporal duration) and resolution (grain size, temporal interval). Although describing climate data scale via these terms is appropriate for most meteorological applications, for ecology and biogeography, climate data of the same spatiotemporal resolution and extent may differ in their relevance to an organism. Here, we propose that climate proximity, or how well climate data represent the actual conditions that an organism is exposed to, is more important for ecological realism than the spatiotemporal resolution of the climate data. Location Temperature comparison in nine countries across four continents; ecological case studies in Alberta (Canada), Sabah (Malaysia) and North Carolina/Tennessee (USA). Time Period 1960–2018. Major Taxa Studied Case studies with flies, mosquitoes and salamanders, but concepts relevant to all life on earth. Methods We compare the accuracy of two macroclimate data sources (ERA5 and WorldClim) and a novel microclimate model ( microclimf ) in predicting soil temperatures. We then use ERA5, WorldClim and microclimf to drive ecological models in three case studies: temporal (fly phenology), spatial (mosquito thermal suitability) and spatiotemporal (salamander range shifts) ecological responses. Results For predicting soil temperatures, microclimf had 24.9% and 16.4% lower absolute bias than ERA5 and WorldClim respectively. Across the case studies, we find that increasing proximity (from macroclimate to microclimate) yields a 247% improvement in performance of ecological models on average, compared to 18% and 9% improvements from increasing spatial resolution 20‐fold, and temporal resolution 30‐fold respectively. Main Conclusions We propose that increasing climate proximity, even if at the sacrifice of finer climate spatiotemporal resolution, may improve ecological predictions. We emphasize biophysically informed approaches, rather than generic formulations, when quantifying ecoclimatic relationships. Redefining the scale of climate through the lens of the organism itself helps reveal mechanisms underlying how climate shapes ecological systems.

Characterizing dog cognitive aging using spontaneous problem-solving measures: development of a battery of tests from the Dog Aging Project - Stephanie H. Hargrave; Emily E. Bray; Stephanie McGrath; Gene E. Alexander; Theadora A. Block; Naomi Chao; Martin Darvas; Laura E. L. C. Douglas; Janet Galante; Brenda S. Kennedy; Breonna Kusick; Julie A. Moreno; et al. (GeroScience, 2024)

Human platelet concentrates treated with microbicidal 405 nm light retain hemostasis activity - Joseph W. Jackson; Pravin R. Kaldhone; Leonid A. Parunov; Caitlin F. Stewart; John G. Anderson; Scott J. MacGregor; Michelle Maclean; Chintamani D. Atreya (Journal of Photochemistry and Photobiology B: Biology, 2024)

Network Analysis Reveals Changes in Dietary Intakes and DNA Methylation in Inflammatory and Obesity-related Cancer Pathways Are Associated with Improvements in Clinical Health Indicators During Behavioral Weight Loss - E. Hill; J. Siebert; I. Konigsberg; P. Jambal; M. Stanislawski; D. Ostendorf; K. Bing; L. Wayland; J. Scorsone; D. Bessesen; P. MacLean; E. Melanson; et al. (Journal of the Academy of Nutrition and Dietetics, 2023)

Forester and Logger Response to Emerald Ash Borer in Massachusetts and Vermont: A Secondary Disturbance - Marla Markowski-Lindsay; Paul Catanzaro; Amanda Robillard; Brett J Butler; David A Orwig; Anthony W D’Amato; Jonathan R Thompson; Danelle M Laflower; Meghan Graham MacLean; Malcolm Itter (Journal of Forestry, 2023)
Forester and logger responses to the invasive emerald ash borer (EAB) could substantially affect regions across the United States. We analyzed forester and logger responses to EAB in Massachusetts and Vermont, exploring characteristics associated with purposeful targeting of substantial ash properties; managing forests differently because of EAB; and regeneration goals. One-third of respondents increased timber sales on ash properties, motivated by ecological, not economic, impacts of EAB. Nearly 60% said EAB changed their management activity in stands with ash; changes influenced by the ecological impact of EAB and not economic factors. Those influenced by EAB’s ecological impact to choose properties with substantial ash were more likely to have increased harvest area size, sawtimber removal, and harvest intensity. Loggers were more likely than foresters to remove small-diameter ash and low-grade trees. Both rated regenerating economically valuable species well adapted to the site as their highest essential priority.

Historical pesticide applications for the treatment of eastern spruce budworm infestations in New Brunswick - Shane Heartz; David A. MacLean; Rob C. Johns; Drew Carleton; Luke Amos‐Binks; Quinn Anderson; Yue Yu; Andrew D. Lewis; Dan Lavigne; Joseph B. Burant; Christopher B. Edge (Ecology, 2023)
Pesticides have been used in Canada since 1945 as part of large‐scale aerial spray applications to control insect pests on forested lands. Some of the pesticides used historically were efficacious, nonselective, persistent, and have led to serious impacts on the environment. A well known, and extensively documented example is the large‐scale aerial spray programs in New Brunswick, Canada. From 1952 to 1993, 97% of the 6.2 million ha of the forested lands of New Brunswick were treated with at least one application of one insecticide, the majority of which were applied to control outbreaks of eastern spruce budworm ( Choristoneura fumiferana ). The most well known insecticide was dichlorodiphenyltrichloroethane (DDT), applied from 1952 to 1968, which still persists in treated soils and adjacent water bodies, and caused the individual and cumulative ecosystem effects that can still be measured today. The insecticides that replaced DDT were nonpersistent and unlikely to be found today. However, during the years of application some of the insecticides were likely to have impacted local ecosystems to some degree. To aid future studies on the efficacy and environmental impact of these insecticides we created a digital spatial data set of known pesticide application in New Brunswick forestry from 1952 to 1993. The data set includes active ingredient, formulation, application rate, tank mix, aircraft type, and other ancillary information. The current version of the data is available on the New Brunswick Department of Natural Resources and Energy Development, GIS Open Data Page and in the supplemental material. Use of the data set for academic and educational purposes is encouraged, provided that both this data paper and the data source are properly cited; the Government of New Brunswick should be acknowledged as the data source (Open Government License http://www.snb.ca/e/2000/data-E.html ).

Associations between physical activity and cognitive dysfunction in older companion dogs: results from the Dog Aging Project - Emily E. Bray; David A. Raichlen; Kiersten K. Forsyth; Daniel E. L. Promislow; Gene E. Alexander; Evan L. MacLean; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; et al. (GeroScience, 2023)

Mechanistic forecasts of species responses to climate change: The promise of biophysical ecology - Natalie J. Briscoe; Shane D. Morris; Paul D. Mathewson; Lauren B. Buckley; Marko Jusup; Ofir Levy; Ilya M. D. Maclean; Sylvain Pincebourde; Eric A. Riddell; Jessica A. Roberts; Rafael Schouten; Michael W. Sears; et al. (Global Change Biology, 2023)
A core challenge in global change biology is to predict how species will respond to future environmental change and to manage these responses. To make such predictions and management actions robust to novel futures, we need to accurately characterize how organisms experience their environments and the biological mechanisms by which they respond. All organisms are thermodynamically connected to their environments through the exchange of heat and water at fine spatial and temporal scales and this exchange can be captured with biophysical models. Although mechanistic models based on biophysical ecology have a long history of development and application, their use in global change biology remains limited despite their enormous promise and increasingly accessible software. We contend that greater understanding and training in the theory and methods of biophysical ecology is vital to expand their application. Our review shows how biophysical models can be implemented to understand and predict climate change impacts on species' behavior, phenology, survival, distribution, and abundance. It also illustrates the types of outputs that can be generated, and the data inputs required for different implementations. Examples range from simple calculations of body temperature at a particular site and time, to more complex analyses of species' distribution limits based on projected energy and water balances, accounting for behavior and phenology. We outline challenges that currently limit the widespread application of biophysical models relating to data availability, training, and the lack of common software ecosystems. We also discuss progress and future developments that could allow these models to be applied to many species across large spatial extents and timeframes. Finally, we highlight how biophysical models are uniquely suited to solve global change biology problems that involve predicting and interpreting responses to environmental variability and extremes, multiple or shifting constraints, and novel abiotic or biotic environments.

Metabolic adaptation and ATP homeostasis in Pseudomonas fluorescens exposed to phosphate stress - Félix Legendre; Alex MacLean; Sujeenthar Tharmalingam; Vasu D. Appanna (World Journal of Microbiology and Biotechnology, 2022)

Correlations between spatial sampling biases and environmental niches affect species distribution models - David J. Baker; Ilya M. D. Maclean; Martin Goodall; Kevin J. Gaston (Global Ecology and Biogeography, 2022)
Aim Spatial sampling biases in biodiversity data arise because of complex interactions between geography, species characteristics and human behaviour, including preferences for or against particular species or habitats; biases are therefore not necessarily independent of the environmental niches of species. We evaluate when correlations between spatial sampling biases and environmental niches are likely to affect species distribution models (SDMs) developed both with and without attempts to correct these biases. Innovation A virtual species and virtual ecologist framework was used to simulate biodiversity data with either no spatial sampling bias or biases that were correlated (positively or negatively) with one of the environmental variables used to define the environmental niches of the species. The environmental variables used to define the species niche were simulated with spatial autocorrelation operating at multiple spatial scales. Virtual samples were then used to model species distributions, with models evaluated based on their ability to rank the suitability of sites correctly. Main conclusions Correlations between spatial sampling bias and environmental niches frequently reduced the rank correlation of model predictions, but the relative importance of these effects varied with species type (greater decline in rank correlation as the environmental niche broadens) and data type (models built using detection/non‐detection data were less affected than those using detection‐only data). Bias‐correction effectiveness varied depending on the structure of the spatial bias but was also highly variable across methods and dependent on data type. The implications of these results are that spatial sampling bias is a greater concern for SDMs where: (1) the distribution of effort is non‐random with respect to an environmental gradient thought to be correlated with a species’ distribution; (2) the species being modelled has a broad environmental niche; and (3) the data for modelling contain only information on detections (i.e., presence only).

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Accounting for inter‐annual variability alters long‐term estimates of climate suitability - Alexandra S. Gardner; Kevin J. Gaston; Ilya M. D. Maclean (Journal of Biogeography, 2021)
Aim Species respond to environmental conditions and so reliable assessments of climate suitability are important for predicting how climate change could alter their distributions. Long‐term average climate data are often used to evaluate the climate suitability of an area, but in these aggregated climate datasets, inter‐annual variability is lost. Due to non‐linearity in species’ biological responses to climate, estimates of long‐term climate suitability from average climate data may be biased and so differ from estimates derived from the average annual suitability over the same period (average response). We investigate the extent to which such differences manifest in a regional assessment of climate suitability for 255 plant species across two 17‐year time periods. Location Cornwall in South‐West England provides a case study. Taxon Plantae. Methods We run a simple mechanistic climate suitability model and derive quantitative estimates of climate suitability for 1984–2000 and 2001–2017. For each period, we run the model using climate data representing average monthly values for that period. We then run the model for each year using monthly climate data for that year and average the annual suitability scores across each period (average response). We compare estimates of climate suitability from these two approaches. Results Average climate data gave higher estimates of suitability than the average response, suggesting bias against years of poor suitability in temporally aggregated climate datasets. Differences between suitability estimates were larger in areas of high climate variability and correlated with species’ environmental requirements, being larger for species with small thermal niches and narrow ranges of precipitation tolerance. Main Conclusions Incorporating inter‐annual variability into climate suitability assessments or understanding the extent to which average climate data might obscure this variance will be important to predict reliably the impacts of climate change on species distributions and should be considered when using mechanistic species distribution models.

Can green schools influence academic performance? - D. Vakalis; C. Lepine; H. L. MacLean; J. A. Siegel (Critical Reviews in Environmental Science and Technology, 2021)

Vulnerability of global biodiversity hotspots to climate change - Brittany T. Trew; Ilya M. D. Maclean (Global Ecology and Biogeography, 2021)
Motivation More than half of Earth's species are contained in a mere 1.4% of its land area, but the climates of many of these biodiversity hotspots are projected to disappear as a consequence of anthropogenic climate change. There is growing recognition that spatio‐temporal patterns of climate in biodiversity hotspots have shaped biological diversity over a variety of historical time‐scales, yet these patterns are rarely taken into account in assessments of the vulnerability of biodiversity hotspots to future climate change. In our review, we synthesize the climatic processes that have led to the diversification of hotspots and interpret what this means in the context of anthropogenic climate change. We demonstrate the importance of mesoclimatic processes and fine‐scale topographical heterogeneity, in combination with climatic variability, in driving speciation processes and maintaining high levels of diversity. We outline why these features of hotspots are crucial to understanding the impacts of anthropogenic climate change and discuss how recent advances in predictive modelling enable vulnerability to be understood better. Location Global. Main conclusions We contend that many, although not all, biodiversity hotspots have climate and landscape characteristics that create fine‐scale spatial variability in climate, which potentially buffers them from climatic changes. Temporally, many hotspots have also experienced stable climates through evolutionary time, making them particularly vulnerable to future changes. Others have experienced more variable climates, which is likely to provide resilience to future changes. Thus, in order to identify risk for global biodiversity, we need to consider carefully the influence of spatio‐temporal variability in climate. However, most vulnerability assessments in biodiversity hotspots are still reliant on climate data with coarse spatial and temporal resolution. Higher‐resolution forecasts that account for spatio‐temporal variability in climate and account better for the physiological responses of organisms to this variability are much needed to inform future conservation strategies.

Global variation in diurnal asymmetry in temperature, cloud cover, specific humidity and precipitation and its association with leaf area index - Daniel T. C. Cox; Ilya M. D. Maclean; Alexandra S. Gardner; Kevin J. Gaston (Global Change Biology, 2020)
The impacts of the changing climate on the biological world vary across latitudes, habitats and spatial scales. By contrast, the time of day at which these changes are occurring has received relatively little attention. As biologically significant organismal activities often occur at particular times of day, any asymmetry in the rate of change between the daytime and night‐time will skew the climatic pressures placed on them, and this could have profound impacts on the natural world. Here we determine global spatial variation in the difference in the mean annual rate at which near‐surface daytime maximum and night‐time minimum temperatures and mean daytime and mean night‐time cloud cover, specific humidity and precipitation have changed over land. For the years 1983–2017, we derived hourly climate data and assigned each hour as occurring during daylight or darkness. In regions that showed warming asymmetry of >0.5°C (equivalent to mean surface temperature warming during the 20th century) we investigated corresponding changes in cloud cover, specific humidity and precipitation. We then examined the proportional change in leaf area index (LAI) as one potential biological response to diel warming asymmetry. We demonstrate that where night‐time temperatures increased by >0.5°C more than daytime temperatures, cloud cover, specific humidity and precipitation increased. Conversely, where daytime temperatures increased by >0.5°C more than night‐time temperatures, cloud cover, specific humidity and precipitation decreased. Driven primarily by increased cloud cover resulting in a dampening of daytime temperatures, over twice the area of land has experienced night‐time warming by >0.25°C more than daytime warming, and has become wetter, with important consequences for plant phenology and species interactions. Conversely, greater daytime relative to night‐time warming is associated with hotter, drier conditions, increasing species vulnerability to heat stress and water budgets. This was demonstrated by a divergent response of LAI to warming asymmetry.

The problem of scale in predicting biological responses to climate - Luca Bütikofer; Karen Anderson; Daniel P. Bebber; Jonathan J. Bennie; Regan I. Early; Ilya M. D. Maclean (Global Change Biology, 2020)
Many analyses of biological responses to climate rely on gridded climate data derived from weather stations, which differ from the conditions experienced by organisms in at least two respects. First, the microclimate recorded by a weather station is often quite different to that near the ground surface, where many organisms live. Second, the temporal and spatial resolutions of gridded climate datasets derived from weather stations are often too coarse to capture the conditions experienced by organisms. Temporally and spatially coarse data have clear benefits in terms of reduced model size and complexity, but here we argue that coarse‐grained data introduce errors that, in biological studies, are too often ignored. However, in contrast to common perception, these errors are not necessarily caused directly by a spatial mismatch between the size of organisms and the scale at which climate data are collected. Rather, errors and biases are primarily due to (a) systematic discrepancies between the climate used in analysis and that experienced by organisms under study; and (b) the non‐linearity of most biological responses in combination with differences in climate variance between locations and time periods for which models are fitted and those for which projections are made. We discuss when exactly problems of scale can be expected to arise and highlight the potential to circumvent these by spatially and temporally down‐scaling climate. We also suggest ways in which adjustments to deal with issues of scale could be made without the need to run high‐resolution models over wide extents.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

A new system to classify global climate zones based on plant physiology and using high temporal resolution climate data - Alexandra S. Gardner; Ilya M. D. Maclean; Kevin J. Gaston (Journal of Biogeography, 2020)
Aim Climate classification systems (CCSs) can be used to predict how species’ distributions might be altered by climate change and to increase the reliability of these estimates is an important goal in biogeographical research. We produce an objective, global climate classification system (CCS) at high temporal resolution based on plant physiology as a robust way to predict how climate change may impact terrestrial biomes. Location Global Taxon Plantae Methods We construct ten climate variables that capture the physiological processes that determine plant distributions and use cluster analysis to present a new global CCS which accounts for variation in these aspects of climate. We use Kappa statistics to compare the distribution of climate zones in a five‐ and six‐cluster CCS constructed using the physiology variables to the popular Köppen‐Geiger and Köppen‐Trewartha CCSs, respectively, and find good correlation in both cases. Results Our CCS highlights ten climate zones for plants. We show that clustering of the physiologically relevant variables reproduces known, present‐day patterns of vegetation but also indicates important areas where zone assignment in our physiological CCSs is different to that of the Köppen systems. Main conclusions The existing Köppen CCSs do not entirely reflect the physiological processes that determine plant distributions. Predictions of climate‐driven changes in plant distributions may thus be unreliable in areas where zone assignment by clustering of physiologically relevant variables is different to that of the Köppen systems. Both the physiological relevance and temporal resolution of climate variables used to construct CCSs should be considered in order to predict reliably how climate change may alter plant distributions and to support an appropriate global response to conserve plant biodiversity for the future.

Biochemical pathways to α-ketoglutarate, a multi-faceted metabolite - F. Legendre; A. MacLean; V. P. Appanna; V. D. Appanna (World Journal of Microbiology and Biotechnology, 2020)

Metabolic adaptation and NADPH homeostasis evoked by a sulfur-deficient environment in Pseudomonas fluorescens - Félix Legendre; Sujeenthar Tharmalingam; Anondo Michel Bley; Alex MacLean; Vasu D. Appanna (Antonie van Leeuwenhoek, 2020)

Predicting future climate at high spatial and temporal resolution - Ilya M. D. Maclean (Global Change Biology, 2020)
Most studies on the biological effects of future climatic changes rely on seasonally aggregated, coarse‐resolution data. Such data mask spatial and temporal variability in microclimate driven by terrain, wind and vegetation, and ultimately bear little resemblance to the conditions that organisms experience in the wild. Here, I present the methods for providing fine‐grained, hourly and daily estimates of current and future temperature and soil moisture over decadal timescales. Observed climate data and spatially coherent probabilistic projections of daily future weather were disaggregated to hourly and used to drive empirically calibrated physical models of thermal and hydrological microclimates. Mesoclimatic effects (cold‐air drainage, coastal exposure and elevation) were determined from the coarse‐resolution climate surfaces using thin‐plate spline models with coastal exposure and elevation as predictors. Differences between micro and mesoclimate temperatures were determined from terrain, vegetation and ground properties using energy balance equations. Soil moisture was computed in a thin upper layer and an underlying deeper layer, and the exchange of water between these layers was calculated using the van Genuchten equation. Code for processing the data and running the models is provided as a series of R packages. The methods were applied to the Lizard Peninsula, United Kingdom, to provide hourly estimates of temperature (100 m grid resolution over entire area, 1 m for a selected area) for the periods 1983–2017 and 2041–2049. Results indicated that there is a fine‐resolution variability in climatic changes, driven primarily by interactions between landscape features and decadal trends in weather conditions. High‐temporal resolution extremes in conditions under future climate change were predicted to be considerably less novel than the extremes estimated using seasonally aggregated variables. The study highlights the need to more accurately estimate the future climatic conditions experienced by organisms and equips biologists with the means to do so.

Opinions of citizen scientists on open access to UK butterfly and moth occurrence data - Richard Fox; Nigel A. D. Bourn; Emily B. Dennis; Richard T. Heafield; Ilya M. D. Maclean; Robert J. Wilson (Biodiversity and Conservation, 2019)

New Proof-of-Concept in Viral Inactivation: Virucidal Efficacy of 405 nm Light Against Feline Calicivirus as a Model for Norovirus Decontamination - Rachael M. Tomb; Michelle Maclean; John E. Coia; Elizabeth Graham; Michael McDonald; Chintamani D. Atreya; Scott J. MacGregor; John G. Anderson (Food and Environmental Virology, 2017)

Determinants of woody encroachment and cover in African savannas - Aisling P. Devine; Robbie A. McDonald; Tristan Quaife; Ilya M. D. Maclean (Oecologia, 2017)

Old concepts, new challenges: adapting landscape-scale conservation to the twenty-first century - Lynda Donaldson; Robert J. Wilson; Ilya M. D. Maclean (Biodiversity and Conservation, 2017)

Fine‐scale climate change: modelling spatial variation in biologically meaningful rates of warming - Ilya M. D. Maclean; Andrew J. Suggitt; Robert J. Wilson; James P. Duffy; Jonathan J. Bennie (Global Change Biology, 2017)
The existence of fine‐grain climate heterogeneity has prompted suggestions that species may be able to survive future climate change in pockets of suitable microclimate, termed ‘microrefugia’. However, evidence for microrefugia is hindered by lack of understanding of how rates of warming vary across a landscape. Here, we present a model that is applied to provide fine‐grained, multidecadal estimates of temperature change based on the underlying physical processes that influence microclimate. Weather station and remotely derived environmental data were used to construct physical variables that capture the effects of terrain, sea surface temperatures, altitude and surface albedo on local temperatures, which were then calibrated statistically to derive gridded estimates of temperature. We apply the model to the Lizard Peninsula, United Kingdom, to provide accurate (mean error = 1.21 °C; RMS error = 1.63 °C) hourly estimates of temperature at a resolution of 100 m for the period 1977–2014. We show that rates of warming vary across a landscape primarily due to long‐term trends in weather conditions. Total warming varied from 0.87 to 1.16 °C, with the slowest rates of warming evident on north‐east‐facing slopes. This variation contributed to substantial spatial heterogeneity in trends in bioclimatic variables: for example, the change in the length of the frost‐free season varied from +11 to −54 days and the increase in annual growing degree‐days from 51 to 267 °C days. Spatial variation in warming was caused primarily by a decrease in daytime cloud cover with a resulting increase in received solar radiation, and secondarily by a decrease in the strength of westerly winds, which has amplified the effects on temperature of solar radiation on west‐facing slopes. We emphasize the importance of multidecadal trends in weather conditions in determining spatial variation in rates of warming, suggesting that locations experiencing least warming may not remain consistent under future climate change.

Climate change impacts and adaptive strategies: lessons from the grapevine - Jonathan R. Mosedale; Kirsten E. Abernethy; Richard E. Smart; Robert J. Wilson; Ilya M. D. Maclean (Global Change Biology, 2016)
The cultivation of grapevines for winemaking, known as viticulture, is widely cited as a climate‐sensitive agricultural system that has been used as an indicator of both historic and contemporary climate change. Numerous studies have questioned the viability of major viticulture regions under future climate projections. We review the methods used to study the impacts of climate change on viticulture in the light of what is known about the effects of climate and weather on the yields and quality of vineyard harvests. Many potential impacts of climate change on viticulture, particularly those associated with a change in climate variability or seasonal weather patterns, are rarely captured. Key biophysical characteristics of viticulture are often unaccounted for, including the variability of grapevine phenology and the exploitation of microclimatic niches that permit successful cultivation under suboptimal macroclimatic conditions. We consider how these same biophysical characteristics permit a variety of strategies by which viticulture can adapt to changing climatic conditions. The ability to realize these strategies, however, is affected by uneven exposure to risks across the winemaking sector, and the evolving capacity for decision‐making within and across organizational boundaries. The role grape provenance plays in shaping perceptions of wine value and quality illustrates how conflicts of interest influence decisions about adaptive strategies within the industry. We conclude by considering what lessons can be taken from viticulture for studies of climate change impacts and the capacity for adaptation in other agricultural and natural systems.

A reply to ‘A meta-database of Holocene sediment cores for England: missing data’ (Tooley 2015) - Andrew J. Suggitt; Richard T. Jones; Chris J. Caseldine; Brian Huntley; John R. Stewart; Stephen J. Brooks; Eleanor Brown; David Fletcher; Phillipa K. Gillingham; Jonathan Larwood; Nicholas A. Macgregor; Barbara Silva; et al. (Vegetation History and Archaeobotany, 2015)

A meta-database of Holocene sediment cores for England - Andrew J. Suggitt; Richard T. Jones; Chris J. Caseldine; Brian Huntley; John R. Stewart; Stephen J. Brooks; Eleanor Brown; David Fletcher; Phillipa K. Gillingham; Jonathan Larwood; Nicholas A. Macgregor; Barbara Silva; et al. (Vegetation History and Archaeobotany, 2015)

Microclimates buffer the responses of plant communities to climate change - Ilya M. D. Maclean; John J. Hopkins; Jonathan Bennie; Callum R. Lawson; Robert J. Wilson (Global Ecology and Biogeography, 2015)
Aim Despite predictions of high extinction risk resulting from climate change, range expansions have been documented more frequently than range retractions, prompting suggestions that species can endure climatic changes by persisting in cool or damp microclimates. We test whether such ‘microrefugia’ exist. Location The U nited K ingdom. Methods We examine fine‐scale changes in the plant communities of a coastal grassland over a 30‐year period in which spring temperatures increased by 1.4 °C. We look at whether changes in community composition and local colonizations and extinctions are related to microclimatic conditions. Results Our findings suggest that while community reassembly was consistent with warming, changes were smaller on cooler, north‐facing slopes. Closer inspection of the patterns of species turnover revealed that species with low temperature requirements were able to persist on cooler slopes, while those with high moisture requirements suffered similar decreases in occupancy across all microclimates. Main conclusions Our results suggest that cooler slopes may act as microrefugia, buffering the effects on plant communities of increases in temperature by delaying extinctions of species with low temperature requirements.

Carnitine transporter CT2 (SLC22A16) is over-expressed in acute myeloid leukemia (AML) and target knockdown reduces growth and viability of AML cells - Yan Wu; Rose Hurren; Neil MacLean; Marcela Gronda; Yulia Jitkova; Mahadeo A. Sukhai; Mark D. Minden; Aaron D. Schimmer (Apoptosis, 2015)

Select microtubule inhibitors increase lysosome acidity and promote lysosomal disruption in acute myeloid leukemia (AML) cells - Dannie Bernard; Marinella Gebbia; Swayam Prabha; Marcela Gronda; Neil MacLean; Xiaoming Wang; Rose Hurren; Mahadeo A. Sukhai; Eunice E. Cho; Morris F. Manolson; Alessandro Datti; Jeffrey Wrana; et al. (Apoptosis, 2015)

Microclimate affects landscape level persistence in the British Lepidoptera - Andrew J. Suggitt; Robert J. Wilson; Tom A. August; Richard Fox; Nick J. B. Isaac; Nicholas A. Macgregor; Michael D. Morecroft; Ilya M. D. Maclean (Journal of Insect Conservation, 2015)

Resolving issues with environmental impact assessment of marine renewable energy installations - Ilya M. D. Maclean; Richard Inger; David Benson; Cormac G. Booth; Clare B. Embling; W. James Grecian; Johanna J. Heymans; Kate E. Plummer; Michael Shackshaft; Carol E. Sparling; Ben Wilson; Lucy J. Wright; et al. (Frontiers in Marine Science, 2014)

Papyrus swamp drainage and the conservation status of their avifauna - Ilya M. D. Maclean; Jeremy P. Bird; Mark Hassall (Wetlands Ecology and Management, 2014)

Basin‐scale phenology and effects of climate variability on global timing of initial seaward migration of Atlantic salmon ( Salmo salar ) - Jaime Otero; Jan Henning L'Abée‐Lund; Ted Castro‐Santos; Kjell Leonardsson; Geir O. Storvik; Bror Jonsson; Brian Dempson; Ian C. Russell; Arne J. Jensen; Jean‐Luc Baglinière; Mélanie Dionne; John D. Armstrong; et al. (Global Change Biology, 2014)
Migrations between different habitats are key events in the lives of many organisms. Such movements involve annually recurring travel over long distances usually triggered by seasonal changes in the environment. Often, the migration is associated with travel to or from reproduction areas to regions of growth. Young anadromous Atlantic salmon ( Salmo salar ) emigrate from freshwater nursery areas during spring and early summer to feed and grow in the North Atlantic Ocean. The transition from the freshwater (‘parr’) stage to the migratory stage where they descend streams and enter salt water (‘smolt’) is characterized by morphological, physiological and behavioural changes where the timing of this parr‐smolt transition is cued by photoperiod and water temperature. Environmental conditions in the freshwater habitat control the downstream migration and contribute to within‐ and among‐river variation in migratory timing. Moreover, the timing of the freshwater emigration has likely evolved to meet environmental conditions in the ocean as these affect growth and survival of the post‐smolts. Using generalized additive mixed‐effects modelling, we analysed spatio‐temporal variations in the dates of downstream smolt migration in 67 rivers throughout the North Atlantic during the last five decades and found that migrations were earlier in populations in the east than the west. After accounting for this spatial effect, the initiation of the downstream migration among rivers was positively associated with freshwater temperatures, up to about 10 °C and levelling off at higher values, and with sea‐surface temperatures. Earlier migration occurred when river discharge levels were low but increasing. On average, the initiation of the smolt seaward migration has occurred 2.5 days earlier per decade throughout the basin of the North Atlantic. This shift in phenology matches changes in air, river, and ocean temperatures, suggesting that Atlantic salmon emigration is responding to the current global climate changes.

A genome wide shRNA screen identifies α/β hydrolase domain containing 4 (ABHD4) as a novel regulator of anoikis resistance - Craig D. Simpson; Rose Hurren; Dahlia Kasimer; Neil MacLean; Yanina Eberhard; Troy Ketela; Jason Moffat; Aaron D. Schimmer (Apoptosis, 2012)

Varying sediment sources (Hudson Strait, Cumberland Sound, Baffin Bay) to the NW Labrador Sea slope between and during Heinrich events 0 to 4 - J. T. Andrews; D. C. Barber; A. E. Jennings; D. D. Eberl; B. Maclean; M. E. Kirby; J. S. Stoner (Journal of Quaternary Science, 2012)
Core HU97048‐007PC was recovered from the continental Labrador Sea slope at a water depth of 945 m, 250 km seaward from the mouth of Cumberland Sound, and 400 km north of Hudson Strait. Cumberland Sound is a structural trough partly floored by Cretaceous mudstones and Paleozoic carbonates. The record extends from ∼10 to 58 ka. On‐board logging revealed a complex series of lithofacies, including buff‐colored detrital carbonate‐rich sediments [Heinrich (H)‐events] frequently bracketed by black facies. We investigate the provenance of these facies using quantitative X‐ray diffraction on drill‐core samples from Paleozoic and Cretaceous bedrock from the SE Baffin Island Shelf, and on the

Recent evidence for the climate change threat to Lepidoptera and other insects - Robert J. Wilson; Ilya M. D. Maclean (Journal of Insect Conservation, 2011)

A Review of the Relative Merits of Conserving, Using, or Draining Papyrus Swamps - Ilya M. D. Maclean; Rosalind R. Boar; Charles Lugo (Environmental Management, 2011)

Climate change causes rapid changes in the distribution and site abundance of birds in winter - ILYA M. D. MACLEAN; GRAHAM E. AUSTIN; MARK M. REHFISCH; JAN BLEW; OLIVIA CROWE; SIMON DELANY; KOEN DEVOS; BERNARD DECEUNINCK; KLAUS GÜNTHER; KARSTEN LAURSEN; MARC VAN ROOMEN; JOHANNES WAHL (Global Change Biology, 2008)
Detecting coherent signals of climate change is best achieved by conducting expansive, long‐term studies. Here, using counts of waders ( Charadrii ) collected from ca. 3500 sites over 30 years and covering a major portion of western Europe, we present the largest‐scale study to show that faunal abundance is influenced by climate in winter. We demonstrate that the ‘weighted centroids’ of populations of seven species of wader occurring in internationally important numbers have undergone substantial shifts of up to 115 km, generally in a northeasterly direction. To our knowledge, this shift is greater than that recorded in any other study, but closer to what would be expected as a result of the spatial distribution of ecological zones. We establish that year‐to‐year changes in site abundance have been positively correlated with concurrent changes in temperature, but that this relationship is most marked towards the colder extremities of the birds' range, suggesting that shifts have occurred as a result of range expansion and that responses to climate change are temperature dependent. Many attempts to model the future impacts of climate change on the distribution of organisms, assume uniform responses or shifts throughout a species' range or with temperature, but our results suggest that this may not be a valid approach. We propose that, with warming temperatures, hitherto unsuitable sites in northeastern Europe will host increasingly important wader numbers, but that this may not be matched by declines elsewhere within the study area. The need to establish that such changes are occurring is accentuated by the statutory importance of this taxon in the designation of protected areas.

Detrimental effects of recent ocean surface warming on growth condition of Atlantic salmon - CHRISTOPHER D. TODD; SARAH L. HUGHES; C. TARA MARSHALL; JULIAN C. MacLEAN; MICHAEL E. LONERGAN; E. MARTIN BIUW (Global Change Biology, 2008)
Ocean climate impacts on survivorship and growth of Atlantic salmon are complex, but still poorly understood. Stock abundances have declined over the past three decades and 1992–2006 has seen widespread sea surface temperature (SST) warming of the NE Atlantic, including the foraging areas exploited by salmon of southern European origin. Salmon cease feeding on return migration, and here we express the final growth condition of year‐classes of one‐sea winter adults at, or just before, freshwater re‐entry as the predicted weight at standard length. Two independent 14‐year time series for a single river stock and for mixed, multiple stocks revealed almost identical temporal patterns in growth condition variation, and an overall trend decrease of 11–14% over the past decade. Growth condition has fallen as SST anomaly has risen, and for each year‐class the midwinter (January) SST anomalies they experienced at sea correlated negatively with their final condition on migratory return during the subsequent summer months. Stored lipids are crucial for survival and for the prespawning provisioning of eggs in freshwater, and we show that under‐weight individuals have disproportionately low reserves. The poorest condition fish (∼30% under‐weight) returned with lipid stores reduced by ∼80%. This study concurs with previous analyses of other North Atlantic top consumers (e.g. somatic condition of tuna, reproductive failure of seabirds) showing evidence of major, recent climate‐driven changes in the eastern North Atlantic pelagic ecosystem, and the likely importance of bottom‐up control processes. Because salmon abundances presently remain at historical lows, fecundity of recent year‐classes will have been increasingly compromised. Measures of year‐class growth condition should therefore be incorporated in the analysis and setting of numerical spawning escapements for threatened stocks, and conservation limits should be revised upwards conservatively during periods of excessive ocean climate warming.

Autotransgenic and allotransgenic manipulation of growth traits in fish for aquaculture: a review - Y. K. Nam; N. Maclean; G. Hwang; D. S. Kim (Journal of Fish Biology, 2008)
It is noteworthy that the use of transgene elements homologous to both the structural gene and promoter region sequences are more effective than heterologous ones for growth hormone (GH) transgenesis in farmed fish species. The generation of autotransgenic fish carrying the GH‐transgene construct (of which elements originate from the same species only) has been given considerable attention as a potential means to produce a desirable fish strain acquiring significantly improved growth phenotype. Currently, several growth‐enhanced autotransgenic lines including mud loach, carp and tilapia, have been developed or are ongoing for aquacultural purpose. This review considers the generation, development and prospects of autotransgenic manipulation of fish growth, comparing the growth performance of currently available autotransgenic fish strains with those of relevant fast‐growing allotransgenic fishes.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Fire danger monitoring using RADARSAT‐1 over northern boreal forests - K. N. Abbott; B. Leblon; G. C. Staples; D. A. Maclean; M. E. Alexander (International Journal of Remote Sensing, 2007)

Salicylic acid mediates resistance to the vascular wilt pathogen Fusarium oxysporum in the model host Arabidopsis thaliana - C. I. Edgar; K. C. McGrath; B. Dombrecht; J. M. Manners; D. C. Maclean; P. M. Schenk; K. Kazan (Australasian Plant Pathology, 2006)

Comparison of reference genes for quantitative real-time polymerase chain reaction analysis of gene expression in sugarcane - Hayati M. Iskandar; Robert S. Simpson; Rosanne E. Casu; Graham D. Bonnett; Donald J. Maclean; John M. Manners (Plant Molecular Biology Reporter, 2004)

Population structure of Litopenaeus schmitti (Decapoda: Penaeidae) from the Brazilian coast identified using six polymorphic microsatellite loci - R. Maggioni; A. D. Rogers; N. Maclean (Molecular Ecology, 2003)
The population structure of the only Litopenaeus species occurring in Brazilian waters, the white shrimp L. schmitti , was surveyed by screening six microsatellite loci. High diversity ( H E = 0.863; average number of alleles per locus = 37.8) was found across eight geographical locations (2°S to 27°S). Estimates of overall F ST ( 0.0060) were low but significantly different from zero ( P F ST pairwise estimates and amova revealed a significant discontinuity around a major biogeographical boundary, near Cabo Frio, at 23°S. This separation may have been caused either by historical or on‐going hydrogeographical and/or selective factors.

Microsatellite markers to assess the influence of population size, isolation and demographic change on the genetic structure of the UK butterfly Polyommatus bellargus - G. L. Harper; N. Maclean; D. Goulson (Molecular Ecology, 2003)
Five microsatellite DNA markers were isolated and used to quangify population genetic structure among a subset of UK populations of the Adonis blue ( Polyommatus bellargus Rottemburg). Specifically, whether population size, degree of isolation or history of bottlenecking in 1976–1978 can explain current patterns of genetic variation. The butterfly is at its northern range limit in the UK, where it exists as a highly fragmented metapopulation on isolated pockets of calcareous grassland. Most populations were affected by a severe bottleneck in the late 1970s, when a drought caused the host plant ( Hippocrepis comosa ) to wilt. Mantel tests and spatial autocorrelation analysis indicated a significant effect of isolation by distance among the UK populations, a relationship that broke down at greater geographical scales (> 23.85 km), probably because of large areas of unsuitable habitat presenting barriers to gene flow. Similarly, amova revealed that variation among geographical regions was almost double that observed within regions. Larger populations were found to support significantly higher levels of genetic diversity, suggesting that small populations may lose genetic diversity through drift. If, as in other butterfly species, low genetic diversity increases the probability of population extinction, then these populations are likely to be under threat. Neither isolation nor a history of bottlenecks appeared to influence genetic diversity. The results indicate that adequate population size a crucial factor in the conservation of genetic diversity in P. bellargus in the UK.

Fish don’t read textbooks: juvenile salmon prove ignorant of foraging theory - A. MacLean; F. A. Huntingford; J. D. Armstrong; G. D. Ruxton (Journal of Fish Biology, 2003)
The rules governing the selection of feeding patches by foraging animals is an area of intense interest. Much work has focussed on the development of theoretical models that predict when individuals should switch patches. Tests of these models have often been conducted in laboratory environments, but it is not clear how much influence patch‐switching decisions have on population‐level parameters such as growth and distribution in more complex natural environments. We used juvenile Atlantic salmon as a model species to investigate the effects of randomly fluctuating food levels on growth and site selection. We used PIT technology to monitor in detail individuals’ patterns of patch use and activity in an artificial stream, at natural densities. This allowed us experimental control of food supplies and sufficient replication, while retaining many features of a natural system. Only a few individuals of high social rank switched patches as predicted by an appropriate foraging model; otherwise, although frequent, patch‐switching was not related to food availability. Thus, while laboratory experiments indicate that this species has the potential to choose foraging sites on the basis of food availability, it is unlikely that this behavioural mechanism is of great importance in natural systems; further tests of foraging models under natural conditions are essential if we are to understand their effects at the level of populations.

A computer‐activated food delivery system for dispensing natural prey items among complex arrays of patches - A. Maclean; M. S. Miles; J. D. Armstrong (Journal of Fish Biology, 2003)
Experimental studies of the foraging ecology of drift‐feeding fishes have been limited in scope because of the lack of systems for dispensing suitable prey items to a number of patches with complex and controlled spatio‐temporal patterns of delivery rate. Here, tests are reported of a computer‐controlled feeding system that performs this requirement with considerable flexibility.

Growth and nutritional trials on transgenic Nile tilapia containing an exogenous fish growth hormone gene - M. A. Rahman; A. Ronyai; B. Z. Engidaw; K. Jauncey; G‐L. Hwang; A. Smith; E. Roderick; D. Penman; L. Varadi; N. Maclean (Journal of Fish Biology, 2001)
In a long‐term growth trial, transgenic tilapia Oreochromis niloticus L. showed a 2·5‐fold increase in growth compared with non‐transgenic siblings. At 7 months, mean mass of transgenic tilapia was 653 g compared with 260 g for non‐transgenic siblings. A significant increase ( P >0·01) in head: total length ratio, viscera‐somatic index and hepato‐somatic index was observed in transgenic fish. Female gonado‐somatic index ( I G) was found to be lower in transgenics than non‐transgenic siblings in both mixed and separate culture conditions. Transgenic male I G values were found to be higher in mixed culture and lower in separate culture than that of their non‐transgenic siblings. Food conversion efficiency was more than 20% greater in the transgenic fish. In a second shorter‐term growth performance trial, the transgenic fish grew to about four times the size of their non‐transgenic siblings. A digestibility trial suggested that transgenic tilapia were more efficient utilizers of protein, dry matter and energy. Apparent digestibility of protein and apparent energy digestibility were higher in the transgenic fish.

Isolation of microsatellite markers from the Adonis blue butterfly ( Lysandra bellargus ) - G. L. Harper; S. Piyapattanakorn; D. Goulson; N. Maclean (Molecular Ecology, 2000)

A suite of highly polymorphic microsatellite markers in turbot ( Scophthalmus maximus L.) with potential for use across several flatfish species - A. Iyengar; S. Piyapattanakorn; D. A. Heipel; D. M. Stone; B. R. Howell; A. R. Child; N. Maclean (Molecular Ecology, 2000)

The promoter of the plant defensin gene PDF1.2 from Arabidopsis is systemically activated by fungal pathogens and responds to methyl jasmonate but not to salicylic acid - John M. Manners; Iris A.M.A. Penninckx; Katrien Vermaere; Kemal Kazan; Rebecca L. Brown; Andrew Morgan; Donald J. Maclean; Mark D. Curtis; Bruno P.A. Cammue; Willem F. Broekaert (Plant Molecular Biology, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Genetic structure of an aphid studied using microsatellites: cyclic parthenogenesis, differentiated lineages and host specialization - P. Sunnucks; P. J. De Barro; G. Lushai; N. MacLean; D. Hales (Molecular Ecology, 1997)
In a previous study, samples of the grain aphid Sitobion avenae (F.) were collected from wheat and adjacent cocksfoot hosts in a population thought to be primarily parthenogenetic, and DNA from individual aphids was analysed with a multilocus technique. Here we have applied single‐locus microsatellites and a mitochondrial DNA marker to a subset of the same DNA extracts, and have made several additional inferences about important genetic and population processes in S. avenae . Microsatellite analysis indicated very high levels of genic and genotypic variation. S. avenae fell into three genotypic groups inferred to be almost noninterbreeding, while analysis of linkage and Hardy‐Weinberg equilibria suggested high levels of sexual recombination within each genotypic group. Host specialization was evident: one lineage was found only on wheat, and one (bearing many alleles inferred to be introgressed from the blackberry‐grass aphid S. fragariae (Walker)) was found only on cocksfoot. The third group of interrelated genotypes was found commonly on both hosts. Although most genotypes were found only once, some were much more numerous in the sample than expected from the frequency of the alleles they contained. This, and rapid temporal changes in genotypic composition of samples, indicates strong selective differences between genotypes and lineages. In the major genotypic group, the commonest genotypes were significantly more homozygous than were rare ones: thus these data may help to explain the frequent observation of homozygous excess in aphid allozymes. The genotype group showing S. avenae ‐like as well as S. fragariae ‐like alleles also carried S. fragariae ‐like mitochondrial DNA in at least 25/31 cases, indicating gender‐asymmetrical hybridization.

Identification of a predominant sequence variant of the T-cell receptor TCRBC1 gene - Sheila J. MacLean; D. M. Gibson (Immunogenetics, 1997)